STATE NARRATIVE DOMINANCE IN TERRORISM REPORTING: A CRITICAL DISCOURSE ANALYSIS OF KOMPAS COVERAGE - Khairunnisa, Putri (Journal of Terrorism Studies, 2025)
This study examines Kompas.com’s news construction of the bombing at the Makassar Cathedral Church on 28 March 2021 by integrating Entman’s Media Framing theory with Fairclough’s Critical Discourse Analysis. Using all news reports published between 28 March and 5 April 2021, the study finds that Kompas frames the event through security-oriented diction, agent–action structures that foreground state authorities as the primary actors, and high-modality statements that minimize uncertainty during the early crisis phase. Intertextual references to previous terrorism cases accelerate the labeling of the perpetrators as part of the JAD network. At the level of discursive practice, reliance on official sources and the speed pressures of digital journalism produce a pattern of authoritative indexing that locks the narrative from the outset. The analysis of social practice further shows that the reporting reproduces the hegemony of state security discourse while marginalizing alternative perspectives. This study highlights the need for source diversification and the strengthening of critical journalism in terrorism coverage.putrikhairunnisa880@gmail.com